Variation in biomass allocation and root functional parameters in response to fire history in Brazilian savannas - Le Stradic, Soizig; Roumet, Catherine; Durigan, Giselda; Cancian, Leonardo; Fidelis, Alessandra (The Journal of ecology, 2021)
Fire is a fundamental ecological factor in savannas because it affects vegetation dynamics and ecosystem functioning. However, the effects of fire on below‐ground compartments, including biomass and root traits, and their regeneration remain poorly understood. In this study, we assess the variation of above‐ and below‐ground plant components along fire‐history gradients in Brazilian open savannas and investigate whether changes in vegetation and soil properties are associated with the responses of below‐ground biomass and root traits. The study was conducted in eight sampling areas of open savanna (campo sujo, i.e. vegetation having low woody cover) within the Cerrado (Brazilian savannas), located along a gradient of time since the last fire (1–34 years); the number of fires that occurred within the past 34 years (0–9 fires) varied by sampling area. In each sampling area, we measured above‐ and below‐ground biomass, root depth distribution, root functional parameters and nutrient levels in the upper soil layers (0–10 cm). Rapid recovery of above‐ground live biomass after a fire was primarily due to resprouting of graminoids. This recovery was associated with an increase in absorptive root biomass in the upper soil layer in the most recently burnt sites, whereas root biomass was unaffected in deeper layers. Root parameters remained constant regardless of fire history but responded to variations in vegetation structure and soil properties. Specific root length (SRL) decreased with K, Mg2+, Al3+, N and C and increased with P concentration. In contrast, root tissue density (RTD) and absorptive root proportion were negatively correlated with soil P. RTD was strongly associated with the above‐ground biomass of graminoids. Soil texture impacted the root system: the proportion of absorptive roots increased with fine sand content in the soil, inversely to transport root biomass. The relationship between fire and soil properties was insignificant. Synthesis. In savannas, fire stimulates absorptive root biomass in response to the higher demand for below‐ground resources. This response is correlated with shoot regrowth after a fire. Variations in morphological root parameters are not directly associated with fire history; instead, they reflect differences in soil chemistry, especially soil P and graminoid biomass changes. Resumo O fogo é um fator ecológico fundamental nas savanas porque afeta a dinâmica da vegetação e o funcionamento do ecossistema. Entretanto, os efeitos do fogo sobre o compartimento subterrâneo, incluindo a biomassa e atributos de raízes, e sua regeneração permanecem mal compreendidos. Neste estudo, caracterizamos os componentes da parte aérea e subterrânea das comunidades de plantas ao longo de gradientes de histórico de queimas no Cerrado e investigamos se as diferenças na vegetação e nas propriedades do solo estão associadas às respostas da biomassa subterrânea e às características das raízes. O estudo foi conduzido em oito áreas de campo sujo de Cerrado (onde a vegetação tem baixa cobertura lenhosa), localizadas ao longo de um gradiente de tempo decorrido desde a última queima (1–34 anos). O número de queimas nos últimos 34 anos (0–9 incêndios) variou entre as áreas de amostragem. Em cada área de amostragem, medimos a biomassa aérea e subterrânea, a distribuição da biomassa de raízes em diferentes profundidades, os parâmetros funcionais das raízes e a composição química do solo na camada superficial (0–10 cm). A rápida recuperação da biomassa aérea viva após uma queima dependeu essencialmente da rebrota de graminoides. Essa recuperação foi associada a um aumento da biomassa de raízes de absorção nos primeiros centímetros do solo nos locais mais recentemente queimados, enquanto a biomassa das raízes não foi afetada nas camadas de solo mais profundas. Os parâmetros funcionais das raízes permaneceram constantes, independentemente do histórico de queimas, mas estiveram associados a diferenças na estrutura da vegetação e em propriedades do solo. O comprimento específico de raiz (SRL) diminuiu com K, Mg2+, Al3+, N e C e aumentou com a concentração de P, enquanto a densidade do tecido radicular (RTD) e a proporção de raízes de absorção foram negativamente correlacionadas com o P. A RTD mostrou‐se fortemente associada à biomassa aérea de graminoides. A textura do solo influenciou o sistema radicular: a proporção de raízes de absorção foi positivamente associada com o conteúdo de areia fina no solo, ao contrário da biomassa das raízes de transporte. A relação entre o histórico de fogo e as propriedades do solo foi insignificante. Síntese. Em savanas, o fogo estimula a produção de biomassa de raízes de absorção em resposta à maior demanda por recursos subterrâneos para dar suporte à rebrota após a queima. Diferenças nos parâmetros morfológicos das raízes não se mostraram diretamente associadas ao histórico do fogo; em vez disso, refletem diferenças na química do solo, especialmente em teor de P e, também, na biomassa de graminoides. Fire stimulated the increase of absorptive root biomass in the upper soil layer in response to the higher demand for below‐ground resources, but did not promote modification of morphological root parameters. Differences in morphological root parameters reflected variation in soil properties, especially soil P, as well as differences in graminoid biomass.